Relationship Between Endothelial Function and the Eliciting Shear Stress Stimulus in Women: Changes Across the Lifespan Differ to Men. Issue 4 (19th February 2019) - Holder, Sophie M.; Brislane, Áine; Dawson, Ellen A.; Hopkins, Nicola D.; Hopman, Maria T. E.; Cable, N. Timothy; Jones, Helen; Schreuder, Tim H. A.; Sprung, Victoria S.; Naylor, Louise; Maiorana, Andrew; Thompson, Andrew; et al.
Abstract : Background: Premenopausal women have a lower incidence of cardiovascular disease, which may partly be due to a protective effect of estrogen on endothelial function. Animal studies suggest that estrogen may also improve the relationship between shear rate (SR) and endothelial function. We aimed to explore the relationship between endothelial function (ie, flow‐mediated dilation [FMD]) and SR (ie, SR area under the curve [SRAUC]) in women versus men, and between pre‐ versus postmenopausal women. Methods and Results: Brachial artery FMD and SRAUC were measured in accordance with expert‐consensus guidelines in 932 healthy participants who were stratified into young adults (18‐40 years, 389 men, 144 women) and older adults (>40 years, 260 men, 139 women). Second, we compared premenopausal (n=173) and postmenopausal women (n=110). There was evidence of a weak correlation between SRAUC and FMD in all groups but older men, although there was variation in strength of outcomes. Further exploration using interaction terms (age‐sex×SRAUC) in linear regression revealed differential relationships with FMD (young women versus young men [β=−5.8 −4, P =0.017] and older women [β=−5.9 −4, P =0.049]). The correlation between SRAUC and FMD in premenopausal women ( r 2 =0.097) was not statistically different from that in postmenopausal women ( r 2 =0.025; Fisher P =0.30). Subgroup analysis using stringent inclusion criteria for health markers (n=505) confirmed a stronger FMD‐SRAUC correlation in young women compared with young men and older women. Conclusions: Evidence for a stronger relationship between endothelial function and the eliciting SR stimulus is present in young women compared with men. Estrogen may contribute to this finding, but larger healthy cohorts are required for conclusive outcomes.